6 - Student Evaluation of Teaching: Bringing Principles into Practice - Khamis, Tashmin; Tennant, Geoff (Journal of Higher Education in Africa, 2022)
Student evaluation of the teaching process is an important quality assurance tool with the potential to give data that can be used to inform the development of courses and guidance of instructors. They have become increasingly important in western countries over the last forty years or so as their results are also used for ‘high stakes’ purposes. This paper examines the background of student evaluations, including reasons – sometimes conflicting – for undertaking them, choice of question items, administration, and analysis and use of results. The design of the Student Evaluation of Teaching used at the Aga Khan University is described; it looks to capture the student voice in a meaningful, helpful and proportionate manner. Data from the pilot stage, which assessed the efficacy of student evaluation of teaching, are given along with pointers for future good practices.